BUDGET RATCHETING ON SIDOARJO REGENCY GOVERNMENT BUDGET REALIZATION (EMPIRICAL STUDY ON SIDOARJO REGENCY GOVERNMENT) - Fauzia, Anugerah Wahyu; Tyas, Erinda Wahyuning; Amanda, Risha Tri; Biduri, Sarwenda (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study investigates the impact of local revenue on regional spending in the aftermath of the COVID-19 pandemic, with budget ratcheting analyzed as a moderating variable. Method: A quantitative approach utilizing secondary data was employed. The study population included all government organizations, with a sample size of 48. Data analysis involved classical assumption testing, simple linear regression, and moderated regression analysis (MRA). Results: The findings reveal that local revenue positively influences regional spending, indicating that higher local revenues lead to increased regional expenditures. However, budget ratcheting does not moderate the relationship between local revenue and regional spending. Novelty: This study highlights the critical role of local revenue in shaping regional spending post-pandemic and emphasizes the limited influence of budget ratcheting as a moderating factor. It further underscores the necessity for regional governments to bolster local economies by fostering community small business activities and exploring potential sources of local revenue to ensure sustainable financial planning and development.